Pengaruh Terapi Akupresur Terhadap Mual Muntah Pada Pasien Kanker Payudara Yang Menjalani Kemoterapi Di Rsup Dr. M. Djamil Padang - Weny Amelia; Defrima Oka Surya; Fitria Alisa; Lola Despitasari; Ria Desnita; Rini Rahmayanti; Viki Yusri; Sarah Afriana (JURNAL KESEHATAN MERCUSUAR, 2023)
Breast cancer is a condition in which cells lose their normal control so that it can result in abnormally rapid and uncontrolled tissue growth. Nausea and vomiting are one of the side effects that often occur in the use of cytostatics in chemotherapy. One of the non-pharmacological nursing interventions to reduce nausea and vomiting scores is acupressure. The purpose of this study was to determine the effect of acupressure therapy on nausea and vomiting scores in breast cancer patients undergoing chemotherapy. This study uses a pre-experimental design with a one-group pre-test post-test design. The sample amounted to 11 respondents with a sampling technique that is purposive sampling. The data processing used in this research is the t-test. The results showed that the mean score of nausea and vomiting before acupressure intervention was 22.46 and the average score of nausea and vomiting after acupressure was 14.27. There is a difference in the score of nausea and vomiting before and after the acupressure intervention with p value 0.000 (p <0.05), meaning that there is an effect of acupressure on the nausea and vomiting score in breast cancer patients undergoing chemotherapy. It is recommended for nursing services to make acupressure intervention as a non-pharmacological therapy in reducing nausea and vomiting scores in breast cancer patients undergoing chemotherapy.